The Representation of the "New Malay": A Study of Selected Films by Rahim Razali (Melayu: Jurnal Antarabangsa Dunia Melayu, 2025)
Film is the best medium for capturing, imagining and reliving important moments in the history of a nation. Director Rahim Razali emerged as one of the prominent f igures of contemporary local arts in the 1980s, leveraging the ideology of national development, particularly in relation to the Malays, and highlighting sociocultural and political realism as central themes in his films. Rahim framed the themes of his films based on the nation’s political and socio-cultural imagination of the 80s which was driven by the New Economic Policy (DEB) and the Bersih, Cekap dan Amanah (BCA) policy. Therefore, this study examines the notion of ‘new Malay’ (Melayu Baharu) born out of the political changes in the 80s by the then Malay-dominated government thorugh the films of Abang (1981) and Matinya Seorang Patriot (1984).This study deploys the Ruling Class Ideology Theory by Marx and Engel (1964), which explores how the society is structured to enable those in power to maintain maximum control over the populace. Furthermore, the interpretive content analysis method is used to enable both the mapping of critical discourse analysis and framing the analysis on the selected films. The f indings demonstrate that Abang provides the social, cultural and political lens on identity of the Malays in the 80s, reflecting the modernisation of the community during the NEP era. Rahim also addressed themes of good governance and anti corruption in the Malay corporate world, particularly in Matinya Seorang Patriot, where the moral integrity emphasised by the BCA policy comes to the forefront. In conclusion, this study finds that Rahim is a dedicated and patriotic filmmaker who served his country and propagated the dominant ideology through his critiques of Malay culture, socio-economy and politics, which makes these films not merely entertaining but also deeply enlightening to his audience.